2022
DOI: 10.28991/cej-2022-08-05-014
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Honeycomb Sandwich Panel Structure using Aluminum Alloy (AL6XN) Material under Blast Loading

Abstract: In this study, we focused on the large inelastic behavior of a sandwich panel made of two solid plates as a stiffener and a honeycomb core shell subjected to blast load. The loading scheme was carried out using an explosive charge bullet mounted at a standoff distance of 100 mm with three mass variations of trinitrotoluene: 1, 2, and 3 kg TNT. The numerical simulations performed using ABAQUS/CAE were validated with the experimental results of a previous study. The geometrical effects of the sandwich panel on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Te efect of several modeling parameters was studied such as mesh sensitivity analysis, and the inclusion of air medium and erosion values on the displacements and damage pattern. Ansori et al [13] numerically investigated the geometrical efects of the sandwich panel on intact and damaged models. Te results showed that the hexagonal core was more resistant to blast loads than the square design.…”
Section: Introductionmentioning
confidence: 99%
“…Te efect of several modeling parameters was studied such as mesh sensitivity analysis, and the inclusion of air medium and erosion values on the displacements and damage pattern. Ansori et al [13] numerically investigated the geometrical efects of the sandwich panel on intact and damaged models. Te results showed that the hexagonal core was more resistant to blast loads than the square design.…”
Section: Introductionmentioning
confidence: 99%
“…This catastrophe is represented by numerous causes such as fire/explosion, collision, grounding, hull damage, and machinery damage/failure resulting in such damage as tearing, plastic deformation, folding, and torsion. Research to improve the safety of transportation [3], especially ships, has been critical in recent years [4][5][6][7]. The methods introduced by researchers for analyzing the structural damage in a ship can be classified into four categories: empirical methods [8], finite element methods [9][10][11][12], experimental methods, and simplified analytical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the response of the geometric structure of a plate to impact and various active loads [5][6][7][8][9][10][11][12][13], including air blast loading, has been carried out over the past few decades. Explosive loading due to landmines and improvised explosive devices (IEDs) poses a signi cant threat to military vehicles and civilian infrastructure.…”
Section: Introductionmentioning
confidence: 99%